Transnasal bile duct catheterisation after endoscopic sphincterotomy: method for biliary drainage, perfusion, and sequential cholangiography. Issue 4 (April 1979) - Cotton, P B; Burney, P G; Mason, R R
Abstract : We describe a method for leaving a catheter in the common bile duct for several days, even weeks, after endoscopic sphincterotomy. This provides reliable biliary drainage, and permits perfusion of the duct with simple fluids or solvents. It reduces the need for instrumental stone extraction and for repeated endoscopy and cholangiography to check whether stones have passed, since transnasal cholangiograms can be performed simply and repeatedly without discomfort.